2013
DOI: 10.1186/1743-422x-10-347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of broadly neutralizing antibody epitopes in the HIV-1 envelope glycoprotein using evolutionary models

Abstract: BackgroundIdentification of the epitopes targeted by antibodies that can neutralize diverse HIV-1 strains can provide important clues for the design of a preventative vaccine.MethodsWe have developed a computational approach that can identify key amino acids within the HIV-1 envelope glycoprotein that influence sensitivity to broadly cross-neutralizing antibodies. Given a sequence alignment and neutralization titers for a panel of viruses, the method works by fitting a phylogenetic model that allows the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Considering the 15% strongest learnt signals for each classifier, we found that several amino acids ( residues ) of the envelope protein were learnt by the classifiers to influence neutralization resistance or susceptibility, which are also supported by literature [ 39 , 53 ]. In Table 2 we present the learnt signals of the classifiers exemplarily for the bNAbs PG9, PG16, 10-669, 10-1074, PGT121, VRC01, and VRC-PG04 that are supported by previous studies.…”
Section: Resultssupporting
confidence: 84%
“…Considering the 15% strongest learnt signals for each classifier, we found that several amino acids ( residues ) of the envelope protein were learnt by the classifiers to influence neutralization resistance or susceptibility, which are also supported by literature [ 39 , 53 ]. In Table 2 we present the learnt signals of the classifiers exemplarily for the bNAbs PG9, PG16, 10-669, 10-1074, PGT121, VRC01, and VRC-PG04 that are supported by previous studies.…”
Section: Resultssupporting
confidence: 84%
“…The antigenicity of these HIV-1 proteins ( Fig. 1A to D and 2A to E ) was determined using samples from human and nonhuman primate vaccine protocols, a panel of HIV-1 monoclonal antibodies (MAbs), and plasma and purified IgG from HIV-1-positive subjects representing multiple HIV-1 clades ( 22 ). Samples from multiple origins were used to provide broad coverage of antibody responses from both infection and vaccination across subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, Walker et al17 do not provide the env sequences from the test panel, which is why we could not predict coreceptor usage for the test panel they used. However, we could test for an R5-bias on neutralization data from sera of patients of the CAPRISA Acute Infection study with PGT-like neutralization potential 19. For one of the sera, the authors showed computationally and through a mutation study that position 316 was highly relevant for neutralization.…”
Section: Resultsmentioning
confidence: 99%